The Effect of Entrepreneurship Knowledge, E-Commerce, Family Environment and Achievement Motivation on Interest In Entrepreneurship of Economic Education Students, Universitas PGRI Sumatera Barat - Meri Rahmania; Wati Wati; Wardani Purnama Sari (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2022)
This study aims to determine how the influence of entrepreneurship knowledge, e-commerce, family environment, and achievement motivation on the entrepreneurial interest of economic education students at Universitas PGRI Sumatera Barat. This research was conducted on students of economics education at Universitas PGRI Sumatera Barat with 100 students who have completed the Entrepreneurship Course with a random sampling technique. This type of research uses descriptive quantitative research. This research was conducted in February 2022. The data analysis technique used multiple linear regression analysis. The results of this study indicate that there is a positive and significant influence between entrepreneurial knowledge and interest in entrepreneurship. There is a positive and significant effect of eCommerce on entrepreneurial interest. In addition, there is a positive and significant influence between family environment and interest in entrepreneurship. There is a positive and significant influence between achievement motivation and entrepreneurial interest and simultaneously entrepreneurial knowledge of the use of e-commerce, family environment, and achievement motivation on student entrepreneurial interest.